Pengaruh Makro Ekonomi, Struktur Modal, Struktur Kepemilikan, Faktor Teknikal terhadap Profitabilitas dengan Total Pendapatan Sebagai Variabel Intervening pada Sub Sektor Perkebunan Di Bursa Efek Indonesia Periode 2014-2020 - Yunan Surono; Muhammad Ade Masyhuri (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to see the relationship between macroeconomic variables, capital structure, ownership structure, technical factors on profitability variables with total income as an intervening variable in the plantation sub-sector stock group on the Indonesia Stock Exchange for the period 2014 – 2020. This study uses SEM (Structural) analysis. Equation Modeling) based on component or variance, namely Partial Least Square (PLS), using Smart PLS 3.0 software. The results showed that 1) macroeconomic variables had no effect on total income. 2) capital structure variable has no effect on total income. 3) ownership structure variable has an effect on total income. 4) technical factor variables have no effect on total income. 5) macroeconomic variables affect profitability. 6) the capital structure variable has no effect on profitability. 7) ownership structure variable has no effect on profitability. 8) technical factor variables affect profitability. 9) Macro economy has no effect on profitability through total income. 10) capital structure has no effect on profitability through total income. 11) ownership structure has no effect on profitability through total income. 12). technical factors have no effect on profitability through total revenue.